Search for dormant black holes in ellipsoidal variables – III. The OGLE BULGE short-period sample. Issue 4 (3rd May 2021) - Gomel, Roy; Faigler, Simchon; Mazeh, Tsevi; Pawlak, Michał
ABSTRACT: This is the third of a series of papers that presents an algorithm to search for close binaries with massive, possibly compact, unseen secondaries. The detection of such a binary is based on identifying a star that displays a large ellipsoidal periodic modulation, induced by tidal interaction with its companion. In the second paper of the series, we presented a simple approach to derive a robust modified minimum mass ratio (mMMR), based on the observed ellipsoidal amplitude, without knowing the primary mass and radius, assuming the primary fills its Roche lobe. The newly defined mMMR is always smaller than the actual mass ratio. Therefore, a binary with an mMMR larger than unity is a good candidate for having a massive secondary, which might be a black hole or a neutron star. This paper considers 10 956 OGLE short-period ellipsoidals observed towards the Galactic bulge. We re-analyse their modulation and identify 136 main-sequence systems with mMMR significantly larger than unity as candidates for having compact-object secondaries, assuming their observed periodic modulations reflect indeed the ellipsoidal effect. Obviously, one needs follow-up observations to find out the true nature of these companions.